2021
DOI: 10.1080/09638199.2021.1951820
|View full text |Cite
|
Sign up to set email alerts
|

Import demand elasticities revisited

Abstract: In this paper, we present import demand elasticities estimated for 167 countries over 5,124 products at the six-digit level of the Harmonised System. Following the semiflexible translog GDP function approach proposed by Kee et al. (2008), we estimate unilateral import demand elasticities for the period 1996-2014. Results are differentiated by country and product characteristics. South Asia and North America are associated with the most elastic import demand. Countries exhibiting the highest average elasticitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This expected increase in trade volumes because of improving importing costs demonstrates the potential trade-enhancing effect of reducing friction at the borders. Sources: 1,3-7 , authors' calculations; 2 , Grübler et al [27]. Notes: 2 , Elasticity of import demand; 3 , change in imports.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This expected increase in trade volumes because of improving importing costs demonstrates the potential trade-enhancing effect of reducing friction at the borders. Sources: 1,3-7 , authors' calculations; 2 , Grübler et al [27]. Notes: 2 , Elasticity of import demand; 3 , change in imports.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of the potential economic gains from improving import costs (with Singapore as the benchmark). Sources: 1,3-7 , authors' calculations; 2 , Grübler et al [27]. Notes: 2 , Elasticity of import demand; 3 , change in imports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A country will import more Malaysian palm oil if Malaysia's price is lower than Indonesia's, and vice versa (Suherman, Suharno, & Harianto, 2016). This is due to the agri-food sector is more sensitive toward price than other sectors like manufacturing (Grübler, Ghodsi, & Stehrer, 2022). Thus, it seems to be important to study the influence of palm oil trade price from Indonesia on China's palm oil demand from Malaysia, hence, this study included this factor in the regression model to complement the past studies where this factor is found absent.…”
Section: Introductionmentioning
confidence: 99%